Western Blot Analyses of Prekallikrein and its Activation Products in Human Plasma - Veloso, Dulce; Colman, Robert W (Thrombosis and Haemostasis, 1991)
Prekallikrein (PK), a zymogen of the contact system, and its activation products, kallikrein (KAL), KAl-inhibitor complexes and fragments containing KAL epitope(s) have been detected in human plasma by immunoblotting with a monoclonal anti-human plasma PK antibody, MAb 13G1L. Detection of antigen-MAb 13G11 complexes with peroxidase-conjugated anti-IgG showed that the two variants of PK (85- and 88-kDa) are the only major antigen species in normal, non-activated plasma. Upon plasma activation with kaolin, the intensity of the PK bands decreased with formation of complexes of KAL with CL inhibitor (C1 INH) and α2-rrtzcroglobulin (α2M) identical to those formed by the purified proteins. Immunoblots of normal plasma showed good correlation between the PK detected and the amount of plasma assayed. Increasing amounts of KAL incubated with a constant volume of PK-deficient plasma showed increasing amounts of KAL and of KAL-C1 INH and KAL-α2M complexes. Complexes of KALantithrombin III (ATIII) and the ratio of KALα2M/ KAL-CL INH were higher in activated CL INH-deficient plasmas than in activated normal plasmas. Protein resolution by 3-12% gradient SDS-PAGE and epitope detection with [125I]MAb 13G11 showed four KALα2M species and a 45-kDa fragment(s) in both surface-activated normal plasma and complexes formed by purified KAL and α2M. Immunoblots of activated plasma also showed bands at the position of KALCL INH and KALATIII complexes. When α1-antitrypsin Pittsburgh (cα1-AT, Pitts) was added to plasma before activation, KAL-α1-ALPitts was the main complex. The non-activated normal plasma revealed only an overloaded PK band. This is the first report of an antibody that recognizes KAL epitope(s) in KAL-α2M, KALATIII and KALa1-α1Pitts complexes and in the 45-kDa fragment(s). Therefore, MAb 13G11 should be useful for studying the structure of these complexes as well as the mechanism of complex formation. In addition, immunoblotting with MAb 13G11 would allow detection of KAl-inhibitor complexes in patient plasmas as indicators of activation of the contact system.